Multicultural Schools Administration of School Administrators in the Digital Age within the Wiang Malika Educational Quality Development Center Under the Chiang Mai Primary Educational Service Area Office 3. - ทองเซ, พิชญาภัค; Yomsungnuan , Junchai; deethung, Sirinnicha; Munkhian, Phuwanat (Journal of MCU Phetchaburi Review, 2026)
This research aims to study Multicultural Schools Administration of School Administrators in the Digital Age within the Wiang Malika Educational Quality Development Center Under the Chiang Mai Primary Educational Service Area Office 3. The population consisted of 112 school administrators and teachers. The research instruments were questionnaires and interviews. Data was analyzed using mean, standard deviation, and content analysis. The research results showed that the overall were at Multicultural Schools Administration of School Administrators in the Digital Age a high level. When considering each aspect, all aspects were found to be at a high level, ranked from highest to lowest mean: communication ability, acceptance of cultural diversity, development of relationships within the organization, and building relationships with the community, respectively. Guidelines for developing culturally diverse school administration practices by school administrators in the digital age were found to be In terms of acceptance of cultural diversity, administrators served as good role models in using technology, promoting professional learning communities (PLCs) and exchanging technological knowledge through peer coaching. This involved colleagues with high technological skills mentoring those with basic technological levels, reducing the technological gap. Furthermore, they inspire, build confidence, and provide guidance in the use of technology. In terms of communication skills, they are skilled managers with creative two-way communication abilities, fostering continuous interaction and focusing on inspirational communication, a positive outlook on change, and constructive feedback from all stakeholders. Regarding internal relationships, they establish clear ethical guidelines and agreements for technology use in collaboration, serving as a model for promoting and driving the ethical and socially responsible use of technology and fostering a culture of collaborative learning. Finally, in building community relationships, they encourage the participation of teachers and staff in community involvement in brainstorming, implementation, decision-making, and shared responsibility. They provide opportunities for parents and community members to play a role and participate in education management. The school serves as a technology learning center, provides academic services, and is an integral part of the community, driving sustainable digital learning and progress together.